Filipinas - Lamangan, Joel.; Viva Films (Firm). ([Quezon City] Viva Films, 2004)
Filipinas tells the story of a family separated by rifts and conflicts. Florencia Filipinas, the matriarch, summons her children in an effort to unite the family once more. The plan backfired, unfortunately, for her children still holds resentment against each other. Past hurts and grievances then surface, a tense atmosphere of conflict hangs in the household. Things get worse when the matriarch's health fails and she slips in a coma. Now for the first time, the siblings become one praying for health.
VCD
Story and screenplay Roy Iglesias, executive producer Vic Del Rosario, Jr., directed by Joel Lamangan
Maricel Soriano, Richard Gomez, Aiko Melendez
Keywords: Drama; Family--Philipines.; Feature films